Digital Dublin: the Water Protests and Social Media in Ireland - Ritter, Christian (AoIR Selected Papers of Internet Research, 2016)
This paper explores how grassroots activists made use of social media during the water protests in the Republic of Ireland between 2014 and 2015. The Irish government envisaged introducing water charges for private households in 2014. Based on a comprehensive discourse analysis of social media content and a series of in-depth interviews with political leaders, this case study provides crucial insights into digital devices facilitating political protests in Irish civil society. The main purpose of the investigation is to gain a better understanding of the possibilities and limitations of digital sociability by examining the use of social media by grassroots organizations. Following the widespread implementation of web 2.0 technologies, online users increasingly engaged in participatory websites that can be conceived as hybrid entities conflating the vernacular discourse and the institutional structure (Howard 2005). The analysis of the data collected revealed how the extensive use of social media during the Irish water protests transformed urban public spaces in Dublin. Firstly, social media carry the potential to empower their users to express their vernacular discourses, shape public debates and influence the political decision making. Secondly, the study indicates that social media enable new digital representations of urban public spaces from below, challenging existing power relations between “old” and “new” media. Based on these findings, I suggest that urban public spaces are increasingly mediated by digital devices, blurring boundaries between different layers of the public sphere, such as physical spaces, print media and virtual environments.